PRODUKSI RUANG SOSIAL MELALUI MURAL DI KOTA DENPASAR - Candra, Ni Made Tanti; Nugroho, Wahyu Budi; Punia, I Nengah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
The existence of murals in public spaces at Denpasar City can be analyzed by the study of sociology. The aim of this study discusses the issues and therefore explaines the problem involved in the presence of murals at Denpasar City. This study uses qualitative research methods with an explanatory analysis of the social space theory of Henri Lafebvre which has three main dimensions: spacial space, representation of space, and representational space. Based on the results of this research, it shows that the existence of murals is currently consistent with the expectation of community and the production of social space through murals in Denpasar city which has been supported by the government of Denpasar City. However, the government has provided space for mural artists to work although the theme for every mural still determined by them, so this condition may led to the collapse production of social space that had been under taken by the mural artists in Denpasar. Keywords: Production of Social Space, Mural, Denpasar City